أثر تنمية القطاع الخاص على التنويع الاقتصادي في الجزائر خلال الفترة (2000-2022) - السخري كريمة; عدائكة أسماء (جامعة الوادي University of Eloued, 2024)
تهدف الدراسة لتحليل وقياس أثر تنمية القطاع الخاص على التنويع الاقتصادي في الجزائر خلال الفترة (2000-2022)، ولتحقيق هذا الغرض تم استخدام المنهجين التحليلي والكمي القياسي. توصلت الدراسة الى أن القيمة المضافة للقطاع الخاص في الاقتصاد الجزائري لم ترق لقيمتها في اقتصاديات دول أخرى، بالإضافة لوجود أثر معنوي لمؤشرات هذا القطاع على التنويع الاقتصادي، دال على قدرته على تحقيق التنويع، وهذا ما بينه الأثر الإيجابي لمدلول مؤشر الاستثمار الخاص على معدل التنويع، إلا أن هناك عوائق في بيئة عمل القطاع الخاص تحول دون ذلك، وهذا ما بينه الأثر السلبي للتمويل المصرفي المقدم للقطاع الخاص ومؤشر حرية الاستثمار على معدل التنويع. Study aims to analyze and measure the impact of the development of private sector on the economic diversification in Algeria (period 2000-2022). To realize this purpose, we used the analytical and quantitative/standard methods. As a result, the study found that added value of private sector in the Algerian economy did not reach the level as in other countries. Furthermore, the moral influence of indexes of this sector in the economic diversification shows that it is able to realize this diversification, as demonstrated by the positive impact of the notion of private investment index on the diversification. But, there are some obstacles in the environment of the private sector that prevent this objective; As shown by the negative impact of bank financing provided to private sector and the index of economic freedom on diversification.
The impact of the development of private sector on the economic diversification in Algeria (Period 2000 -2022)
Keywords: تنويع إقتصادي; قطاع خاص; Economic diversification; Private sector